If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -7a = 8 Combine like terms: 3a + -7a = -4a -4a = 8 Solving -4a = 8 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '-4'. a = -2 Simplifying a = -2
| -3y=18-9(-2) | | 3a-7whena=8 | | -3y=18-9(0) | | 6.2*3= | | -3y=18-9(2) | | 184=23p | | 2(7)=(x+9)2/3 | | 2(-6+4x)=-84 | | 7a*3a*10B= | | y=2*0+(-2) | | 2(7)=(x+9)2 | | 173-5x=40x+18 | | 7t-4*2t+3t*4/2 | | 10+p=3 | | 6-2(4x)+7=0 | | 5(-2)=y+6 | | 7a*3a= | | 5(0)=y+6 | | 4-9p=49 | | 3/4+5/3 | | 5(2)=y+6 | | 9*n=53 | | 2y-6.2+y=8.8 | | -4+8X=5+2X | | 2(m+5)=28 | | 12+(21-6)/3 | | (4y+3)-(-3y-6)=-2 | | -2(6)+9=-(9)-3 | | -2(-12)+9=-(0)-3 | | 4(x-6)+2=6x-6 | | 5x-1+-2x+7=9 | | 65-98+(85-6x)=9 |